2009
DOI: 10.4040/jkan.2009.39.6.860
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Patient Discomfort after Coronary Angiography

Abstract: Purpose:The purpose of this study was to identify the factors that predict discomfort after coronary angiography or percutaneous coronary intervention (PCI) among hospitalized patients. Methods: A total of 203 patients who underwent coronary angiography or PCI were recruited from C hospital located in S city, J province, from June through August 2008. The level of discomfort was measured and standardized by two instruments, discomfort questionnaire and the Visual Analogue Scale (VAS). Results: Stepwise multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…The experimental group had less overall anxiety at the post-test compared to the control group, suggesting that this relaxation intervention may have reduced anxiety by the end of the procedure. These results were consistent with findings demonstrating a significant reduction in anxiety scores when music therapy was applied to coronary angiogram patients 11 and patients under spinal anaesthesia during surgery. 5 Another study by Nilsson showed no significant reduction in anxiety in cardiac surgery patients who were allowed to listen to music selected in advance by the researchers, 20 which contradicts our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The experimental group had less overall anxiety at the post-test compared to the control group, suggesting that this relaxation intervention may have reduced anxiety by the end of the procedure. These results were consistent with findings demonstrating a significant reduction in anxiety scores when music therapy was applied to coronary angiogram patients 11 and patients under spinal anaesthesia during surgery. 5 Another study by Nilsson showed no significant reduction in anxiety in cardiac surgery patients who were allowed to listen to music selected in advance by the researchers, 20 which contradicts our results.…”
Section: Discussionsupporting
confidence: 90%
“…9 The randomisation sequence was created with the R software random number generator using the permuted block design at a 1:1 allocation ratio to the experimental or control group after admission for interventional cardiac catheterisation. 10 The calculation of the sample size was based on a study by Park et al, 11 with the following assumptions concerning a repeated measure analysis of variance for the primary endpoint with G*power 3.1 software: estimated effect (f) 0.18, a significance level of 5%, and power of 95%. These assumptions resulted in a minimum sample size of 82 participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Esse pacientes também foram menos propensos a se queixarem de desconforto. 16 Por fim, torna-se importante lembrar que cada paciente tem particularidades, como patologias de coluna vertebral preexistentes (hérnia de disco e cirurgias anteriores), dificuldade urinária prévia (retenção urinária e hiperplasia de próstata), maior sensibilidade à dor, fraqueza, dificuldade motora e cognitiva, o que, muitas vezes, está relacionado à idade avançada e/ou a doenças associadas. Essas informações devem ser investigadas pela equipe de profissionais antes do procedimento, para que seja realizado um planejamento individualizado para minimizar os desconfortos.…”
Section: Discussionunclassified
“…To reduce the anxiety of patients with angiography, easing discomfort can be helpful (Trotter et al, 2011). In a study that investigated the factors that influence patient discomfort after angiography, amount of pre‐information most highly predicted level of discomfort (Park & Choi, 2009). Therefore, it is necessary to consider the anxiety and discomfort of patients undergoing cerebral angiography as a major nursing problem, and nursing intervention is needed.…”
Section: Introductionmentioning
confidence: 99%